1996
DOI: 10.1128/aem.62.2.725-727.1996
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of urease-positive Vibrio parahaemolyticus in Kanagawa, Japan, with specific reference to presence of thermostable direct hemolysin (TDH) and the TDH-related-hemolysin genes

Abstract: A total of 132 strains of V. parahaemolyticus isolated from patients and from the suspected causal food items of past food poisoning cases occurring in Kanagawa Prefecture, Japan, were examined for the ability to hydrolyze urea, with specific reference to the presence of the thermostable direct hemolysin gene (tdh) and the gene for thermostable direct hemolysin-related hemolysin (trh). Ten strains belonging to five different Oantigen serotypes were positive for urea hydrolysis (UH ؉), and four of these strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 12 publications
3
14
0
1
Order By: Relevance
“…Also, it is noteworthy that the presence of either tdh or trh, or both, correlated directly with the production of urease, suggesting that these markers in combination can be used to identify and track potentially virulent strains of this pathogen in oysters (Kaysner et al Table 1 1994; Iida et al 1998;DePaola et al 2000). Several studies have reported that in many V. parahaemolyticus strains, the haemolysin-producing genes, tdh or trh, are located very close on the chromosome to the ure gene that codes for urease (Kaysner et al 1994;Osawa et al 1996;Okitsu et al 1997;Iida et al 1998;Park et al 2000). Therefore, it is apparent that the identification of the haemolysin-producing genes as determined by the multiplex PCR, along with the positive reaction for urease, could be used as an indicator of potentially virulent strains of this pathogen in shellfish.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is noteworthy that the presence of either tdh or trh, or both, correlated directly with the production of urease, suggesting that these markers in combination can be used to identify and track potentially virulent strains of this pathogen in oysters (Kaysner et al Table 1 1994; Iida et al 1998;DePaola et al 2000). Several studies have reported that in many V. parahaemolyticus strains, the haemolysin-producing genes, tdh or trh, are located very close on the chromosome to the ure gene that codes for urease (Kaysner et al 1994;Osawa et al 1996;Okitsu et al 1997;Iida et al 1998;Park et al 2000). Therefore, it is apparent that the identification of the haemolysin-producing genes as determined by the multiplex PCR, along with the positive reaction for urease, could be used as an indicator of potentially virulent strains of this pathogen in shellfish.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between urease production and possession of the trh gene suggests that urease production can be used as one of the virulence markers. The correlation was perfect in some of the studies (12,24,30,32) but was not in other studies (26,31). Unlike in the tdh genes, significant nucleotide sequence variation exists in the trh genes in different strains isolated in Asia, and the trh genes could be clustered into two subgroups, trh1 and trh2, which share 84% sequence identity (11,18).…”
mentioning
confidence: 91%
“…The KP-negative phenotype of the Ureϩ strains was pointed out in some of the reports (2,10,13). Very recent reports on examinations of clinical strains isolated in Asian countries and Brazil indicated that the ratio of Ureϩ strains among the clinical strains is gradually increasing and that a strong correlation exists between urease production and the presence of the trh gene rather than that of the tdh gene (12,24,26,(30)(31)(32). The correlation between urease production and possession of the trh gene suggests that urease production can be used as one of the virulence markers.…”
mentioning
confidence: 99%
“…Molecular epidemiological studies revealed that not only strains carrying the tdh gene but strains carrying a trh gene or both genes are strongly associated with gastroenteritis (10,29). Recently, proportion of trh-bearing strains among clinical strains has been increasing and a very strong correlation exists between the presence of the trh gene and urease production, an unusual characteristic for V. parahaemolyticus (12,(24)(25)(26)(30)(31)(32). The urease-positive strains have been isolated in various parts of the world (1,2,5,9,13,23).…”
mentioning
confidence: 99%